Actualization of an efficient throttleable laser propulsion mode. (15th April 2021) - Zhang, Haonan; Duan, Buren; Wu, Lizhi; Hua, Zuohao; Bao, Zijing; Guo, Ning; Ye, Yinghua; Galfetti, Luciano; DeLuca, Luigi T.; Shen, Ruiqi
Abstract: Conventional propulsion systems are difficult to change between propelling and non-propelling modes. Throttleable propulsion that results from the control of the input energy is a significant further step toward application in various space missions. We present our work on a novel propulsion mode producing throttleable thrust under the control of our low power CW laser. This photosensitive propellant is fully capable of repeated ignition and interruption, while generating gases that are more environmentally friendly with decreased solid residues. Laser ignition and combustion performance of such modes are characterized. Laser-controlled combustion behavior examples are shown and discussed. These results show potential applications in many aspects of space missions, such as maneuvers in space, attitude control, orbit raising and microsatellite deorbiting. Graphical abstract: Image 1 Highlights: The propulsion mode produces throttleable thrust efficiently by controlling low-power CW laser. The photosensitive propellant proposed features repeated ignition and interruption with clean generated gases. Good ignition and combustion performances under laser radiation are verified.